Respuesta :

Given: (a) [tex]2(x+3)=2x+6[/tex] and (b) [tex]4(y-3)=4y-12[/tex].

To find: The expanded form of the given expressions.

(c) [tex]4(m+n)=4m+4n[/tex]       (using [tex]a(b+c)=ab+ac[/tex])

(d) [tex]3(5-q)=15-3q[/tex]           (using [tex]a(b-c)=ab-ac[/tex])

(e) [tex]5(2c+1)=10c+5[/tex]          (using [tex]a(b+c)=ab+ac[/tex])

(f) [tex]3(2x-5)=6x-15[/tex]          (using [tex]a(b-c)=ab-ac[/tex])

(g) [tex]7(4b-1)=28b-7[/tex]          (using [tex]a(b-c)=ab-ac[/tex])

(h) [tex]3(2x+y-5)=3((2x+y)-5)[/tex]

⇒[tex]3(2x+y-5)=3(2x+y)-15[/tex]         (using [tex]a(b-c)=ab-ac[/tex])

⇒[tex]3(2x+y-5)=6x+3y-15[/tex]            (using [tex]a(b+c)=ab+ac[/tex])

(i) [tex]2(6a-4b+3)=2((6a-4b)+3)[/tex]

⇒[tex]2(6a-4b+3)=2(6a-4b)+6[/tex]         (using [tex]a(b+c)=ab+ac[/tex])

⇒[tex]2(6a-4b+3)=12a-8b+6[/tex]            (using [tex]a(b-c)=ab-ac[/tex])

(j)[tex]6(m+n+p)=6((m+n)+p)[/tex]

⇒ [tex]6(m+n+p)=6(m+n)+6p[/tex]           (using [tex]a(b+c)=ab+ac[/tex])

⇒ [tex]6(m+n+p)=6m+6n+6p[/tex]            (using [tex]a(b+c)=ab+ac[/tex])

(k) [tex]y(y+2)=y^2+2y[/tex]          (using [tex]a(b+c)=ab+ac[/tex])

(l) [tex]g(g-3)=g^2-3g[/tex]           (using [tex]a(b-c)=ab-ac[/tex])

(m) [tex]n(4-n)=4n-n^2[/tex]        (using [tex]a(b-c)=ab-ac[/tex])

(n) [tex]a(b+c)=ab+ac[/tex]           (using [tex]a(b+c)=ab+ac[/tex])

(o) [tex]s(3s-4)=3s^2-4s[/tex]        (using [tex]a(b-c)=ab-ac[/tex])

(p) [tex]2x(x+5)=2x^2+10x[/tex]     (using [tex]a(b+c)=ab+ac[/tex])

(q) [tex]4y(x-3)=4xy-12y[/tex]      (using [tex]a(b-c)=ab-ac[/tex])

(r) [tex]5a(2b-5)=10ab-25a[/tex]     (using [tex]a(b-c)=ab-ac[/tex])

(s) [tex]4a(3b+2c)=12ab+8ac[/tex]    (using [tex]a(b+c)=ab+ac[/tex])

(t) [tex]5p(4p-5q)=20p^2-25pq[/tex]    (using [tex]a(b-c)=ab-ac[/tex])